Comparing the efficacy of intravenous ketorolac versus intravenous ibuprofen in relieving renal colic pain; a randomized clinical trial - Seyed Hossein Shaker; Seyed Ahmad Borghei (Society of Diabetic Nephropathy Prevention, 2018)
Introduction: Various therapies have been used to relieve or improve the urinary colic pain, but many of these treatments have been limited due to side effects associated with the drugs. In this regard, opioid drugs and nonsteroidal anti-inflammatory drugs (NSAIDs) have a higher priority than other treatments. Objectives: The aim of the present study was to compare the level of pain relief from renal stones after the administration of two types of NSAIDs, including intravenous ibuprofen versus intravenous ketorolac. Patients and Methods: In this clinical trial (identifier: IRCT20180108038276N1), 70 patients with renal colic pain were randomly treated with intravenous ketorolac (30 mg, n = 35) or with intravenous ibuprofen (800 mg, n = 35). The patient's pain severity was assessed by the visual analogue scaling (VAS) method before and 20 and also 60 minutes after interventions. Results: Although pain severity considerably reduced within 60 minutes of prescribing ibuprofen and ketorolac, the trend of the change in pin score was not different between the two groups (P = 0.734). We found no significant difference in appearance of some side effects including nausea and vomiting, requiring use of ondansetron, need to prescribe additional analgesics. However epigastric pain and need to administrating H2 blockers were not revealed in the group receiving ketorolac, but these complications were found in 25.7% of the patients received ibuprofen indicating a significant difference (P = 0.002). Conclusion: A single dose administration of both intravenous ketorolac and ibuprofen is associated with significant improvement in renal colic pain within one hour after administration. However, due to the lower incidence of gastrointestinal complications in the administration of ketorolac compared to ibuprofen, the use of ketorolac in treatment and relief of renal colic pains is preferable.